JOB COMPETENCY MODELING AT AGROINDUSTRIAL COMPANY BY USING MULTI RATER AHP - Alex Denni, Irawadi Jamaran, Aji Hermawan dan Yandra Arkeman (Department of Agroindustrial Technology, Bogor Agricultural University, 2010)
ABSTRACT Agroindustry in the global economy are challenged with transformation process from industrial era to knowledge and information era. Several studies have shown that management strategy of human resource that are directly related to the competence of business people has become the choice of most organizations. However, those studies have not explained how the process of competency development is done in the organization's efforts to survive and grow. This study applied multi-rater AHP method in a local company producing ethanol to develop job competency modeling. This study used analysis descriptive method with multi-rater AHP as its tool. Unstructured issues in this company were simplified into sections and arranged in hierarchy based on the level of interest through synthesis variables. This study shows that the number of managerial competencies was ranging from 5 to 15 competencies and there were seven core competencies. The research findings are expected to have implications on companies or organizations from various agro-industries in the process of developing competency models. The organization's management was expected to make the findings as a reference for the recruitment, placement, promotion, transfer, development and provision of compensation to employees fairly and effectively to support its business strategy. Key words: agroindustry, job competency model, multi rater AHP